2019
DOI: 10.1111/ecog.04408
|View full text |Cite
|
Sign up to set email alerts
|

Time of emergence of novel climates for North American migratory bird populations

Abstract: To better understand the ecological implications of global climate change for species that display geographically and seasonally dynamic life‐history strategies, we need to determine where and when novel climates are projected to first emerge. Here, we use a multivariate approach to estimate time of emergence (ToE) of novel climates based on three climate variables (precipitation, minimum and maximum temperature) at a weekly temporal resolution within the Western Hemisphere over a 280‐yr period (2021–2300) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…For species such as these, it is unknown if range gains in new locations will be sufficient for sustaining populations, given the rapid nature of climate change and the time it takes to establish populations. Lastly, novel climates aren't projected to peak in the non-breeding season until the first half of the next century [101], suggesting that more changes are to come beyond the temporal extent of our projections.…”
Section: Discussionmentioning
confidence: 94%
“…For species such as these, it is unknown if range gains in new locations will be sufficient for sustaining populations, given the rapid nature of climate change and the time it takes to establish populations. Lastly, novel climates aren't projected to peak in the non-breeding season until the first half of the next century [101], suggesting that more changes are to come beyond the temporal extent of our projections.…”
Section: Discussionmentioning
confidence: 94%
“…Our results indicate that migrants are sensitive to the dynamics of their aerial environment and their behaviour and movement properties are strongly affected by local meteorological conditions. Changing atmospheric patterns due to climate change may thus result in changes in migration route selection of migrating white storks, with possible implications for population dynamics (La Sorte, Fink, & Johnston, ) and conservation (Wilcove & Wikelski, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of other species have found individuals to be highly repeatable in their migration schedule, particularly in their pre-breeding movements (Stanley et al 2012, Conklin et al 2013, and individuals may use weather conditions to inform migratory timing (Both 2010, Schmaljohann et al 2012. Correlations between weather conditions at breeding and wintering sites are likely to provide cues for migratory birds to adjust their migration schedule (Saino & Ambrosini 2008), but their usefulness may be reduced due to the spatial variability of climate change (La Sorte et al 2019). It is most likely that both body condition and the provision of cues influence arrival dates, given that individuals may be repeatable in migration schedule but less so in the route taken, which is presumably dependent on ground conditions (Stanley et al 2012).…”
Section: Discussionmentioning
confidence: 99%